The medium term outcome of chronic dialysis in children under the age of two. (4th April 2011) - Jones, H E; Clothier, J C; Rees, L; Shroff, R; Ledermann, S E; Reid, C J D; Sinha, M D; Hulton, S; Inward, C
Abstract : Aims: Outcome data for children under the age of 2 years receiving renal replacement therapy is limited. The aim of this study was to examine modality, duration and outcome in this cohort. Methods: A retrospective case-note and UK Renal Registry review of all children commenced on dialysis for Chronic Kidney Disease stage 5 at under 2 years of age from two paediatric nephrology centres between January 2005 and December 2009. Data are presented as median (range). Results: 31 patients were identified (61% male). 48% were diagnosed antenatally. Commonest diagnoses were dysplasia±obstruction (45%), congenital nephrosis (23%) and metabolic (10%). 32% of patients had significant co-morbidities. Dialysis (peritoneal dialysis (PD) in 81%) was initiated at age 218 (3–634) days; 65% were aged <1 year. The weight at start was 7 kg (1.1–12.4 kg). 74% had a gastrostomy of which 48% were prior to and 52% after dialysis was commenced. Over 17.9 (1.1–57.8) months 42% of patients changed dialysis modality. Catheter related complications including peritonitis were common (46 episodes among 27 patients; 1 per 311 patient days on PD). Five PD patients had no infective episodes. Number of catheters required per patient was 2 (1–4) for PD and 4 (1–6) for haemodialysis. Time from initial PD catheter insertion to discharge home was 63 (7–140) days. Time on dialysis prior to transplantation was 492 (201–1161) days and spent in hospital pre-transplantation was 76 (13–199) days. As of 30 November 2010, 29% of patients remain on dialysis (55% awaiting a deceased donor transplant, 6% have planned living donor), 48% have received a functioning transplant (67% live-related) and 23% have died (1 treatment withdrawal, 3 sepsis, 1 bowel perforation, 2 perioperatively). The patients receiving a live-related transplant were 1.9 (1.5–2.3) years and 11.4 (10–13) kg at time of transplantation. Conclusion: Mortality and morbidity was high in this group of under 2 year olds in CKD 5. PD was the most common treatment but complications of dialysis were common, change of modality was frequently necessary and a significant amount of time was spent in hospital.